2017
DOI: 10.1017/age.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Public acceptance of coastal zone management efforts: The role of citizen preferences in the allocation of funds

Abstract: We investigate allocation of funds by citizens across management options addressing impairments to coastal water quality. We study systematic variation in citizen allocation of funds to adaptive versus preventative strategies including the impact of referundum choices and test whether allocations will be impacted by cuing in the design of the referendum. Two key policy insights from our results: citizens who vote no on a water quality referendum have different preferences over allocating funds and providing cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The contingent allocation method (Evans et al 2017, Soguel et al 2020) confronts individuals with a hypothetical situation in which they have full power to allocate budgetary resources, for example 100 units in total. Thus, the aim is not, as in the contingent valuation method (CVM), to measure the trade-off between a given amenity to be valued and other goods and services under an individual budget constraint (i.e., a marginal rate of substitution).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The contingent allocation method (Evans et al 2017, Soguel et al 2020) confronts individuals with a hypothetical situation in which they have full power to allocate budgetary resources, for example 100 units in total. Thus, the aim is not, as in the contingent valuation method (CVM), to measure the trade-off between a given amenity to be valued and other goods and services under an individual budget constraint (i.e., a marginal rate of substitution).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on budget allocation have either been general, focusing on budget allocation between different sectors (Koford 2009, Soguel et al 2020, or when sector specific, they have in most cases focused on health care or education (Bombard et al 2011, Skedgel et al 2013, Costa-Font et al 2015. Applications related to the environment or natural resources have been rare (Evans et al 2017) and few studies have focused on budget allocation in the agricultural sector (Gómez-Limón and Atance 2004, Rocamora-Montiel et al 2014, Mittenzwei et al 2016. The knowledge gap is not only in measuring preferences, which would be interesting from a policy planning perspective, but also, as Ozdemir et al (2016) argue, in the collection and analysis of respondent socioeconomic characteristics, which could provide policy makers with useful information about supporters and opponents among different budget alternatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intent is to provide guidance to policy makers to maximize social benefits. Combining the notion of willingness to pay and the budget allocation, Evans et al (2017) ask a referendum contingent valuation question with an open‐ended allocation of funds follow‐up question for coastal water quality. They find that budget allocations differ for those who voted in favor of the policy in the referendum compared to those who voted against.…”
Section: Citizen Preferences and Fisheries Managementmentioning
confidence: 99%
“…(2010), the US Water Research Foundation (2011), and, in the context of coastal flooding, Evans et al . (2017). As will be discussed below, new regulatory drivers which motivate better understanding of customer priorities have recently come to the fore in the England & Wales water sector, thereby providing a policy setting for the study reported here.…”
Section: Introductionmentioning
confidence: 99%